Tìm x a) 4x^2 + 20x = -25 b) x^2.(x-6) + 12x = 8
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b:
ĐKXĐ: x>0
\(\Leftrightarrow\left(\sqrt{x}+\dfrac{1}{\sqrt{x}}\right)^2-2-4\left(\sqrt{x}+\dfrac{1}{\sqrt{x}}\right)+6=0\)
\(\Leftrightarrow\left(\sqrt{x}+\dfrac{1}{\sqrt{x}}-2\right)^2=0\)
\(\Leftrightarrow x+1-2\sqrt{x}=0\)
=>x=1
a) ta có \(\sqrt{12x^2+12x+19}+\sqrt{20x^2+20x+14}=-4x^2-4x+6\)
\(\Leftrightarrow\sqrt{12\left(x+\dfrac{1}{2}\right)^2+16}+\sqrt{20\left(x+\dfrac{1}{2}\right)^2+9}=-\left(2x+1\right)^2+7\)ta có : \(VT\ge\sqrt{16}+\sqrt{9}=7\) và \(VT\le7\)
\(\Rightarrow VT=VP\) \(\Leftrightarrow x=\dfrac{-1}{2}\) vậy \(x=\dfrac{-1}{2}\)
b) điều kiện \(x>0\)
ta có : \(\left(x+\dfrac{1}{x}\right)-4\left(\sqrt{x}+\dfrac{1}{\sqrt{x}}\right)+6=0\)
\(\Leftrightarrow\left(\sqrt{x}+\dfrac{1}{\sqrt{x}}\right)^2-4\left(\sqrt{x}+\dfrac{1}{\sqrt{x}}\right)+4=0\)
\(\Leftrightarrow\left(\sqrt{x}+\dfrac{1}{\sqrt{x}}-2\right)^2=0\) \(\Leftrightarrow\sqrt{x}+\dfrac{1}{\sqrt{x}}-2=0\)
\(\Leftrightarrow\sqrt{x}+\dfrac{1}{\sqrt{x}}=2\Leftrightarrow\dfrac{x+\sqrt{x}}{\sqrt{x}}=2\Leftrightarrow x+\sqrt{x}=2\sqrt{x}\)
\(\Leftrightarrow x-\sqrt{x}=0\Leftrightarrow\sqrt{x}\left(\sqrt{x}-1\right)=0\) \(\Leftrightarrow\left[{}\begin{matrix}\sqrt{x}=0\\\sqrt{x}-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\left(L\right)\\x=1\left(N\right)\end{matrix}\right.\)
vậy \(x=1\)
b:
ĐKXĐ: x>0
\(\Leftrightarrow\left(\sqrt{x}+\dfrac{1}{\sqrt{x}}\right)^2-2-4\left(\sqrt{x}+\dfrac{1}{\sqrt{x}}\right)+6=0\)
\(\Leftrightarrow\left(\sqrt{x}+\dfrac{1}{\sqrt{x}}-2\right)^2=0\)
\(\Leftrightarrow x+1-2\sqrt{x}=0\)
=>x=1
a: Ta có: \(\sqrt{\left(x-3\right)^2}=3-x\)
\(\Leftrightarrow\left|x-3\right|=3-x\)
\(\Leftrightarrow x-3\le0\)
hay \(x\le3\)
b: Ta có: \(\sqrt{4x^2-20x+25}+2x=5\)
\(\Leftrightarrow\left|2x-5\right|=5-2x\)
\(\Leftrightarrow2x-5\le0\)
hay \(x\le\dfrac{5}{2}\)
c \(\frac{\left(2x-4\right)\left(x-3\right)}{\left(x-2\right)\left(3x^2-27\right)}=\frac{2\left(x-2\right)\left(x-3\right)}{3\left(x-2\right)\left(x^2-9\right)}\)
\(=\frac{2\left(x-2\right)\left(x-3\right)}{3\left(x-2\right)\left(x-3\right)\left(x+3\right)}=\frac{2}{3\left(x+3\right)}\)
d, \(\frac{x^2+5x+6}{x^2+4x+4}=\frac{\left(x+2\right)\left(x+3\right)}{\left(x+2\right)^2}=\frac{x+3}{x+2}\)
Tương tự với a ; b
Bài 1.
\(a\Big) 9(4x+3)^2=16(3x-5)^2\\\Leftrightarrow 9[(4x)^2+2\cdot 4x\cdot3+3^2]=16[(3x)^2-2\cdot3x\cdot5+5^2]\\\Leftrightarrow9(16x^2+24x+9)=16(9x^2-30x+25)\\\Leftrightarrow 144x^2+216x+81=144x^2-480x+400\\\Leftrightarrow (144x^2-144x^2)+(216x+480x)=400-81\\\Leftrightarrow 696x=319\\\Leftrightarrow x=\dfrac{11}{24}\\Vậy:x=\dfrac{11}{24}\\---\)
\(b\Big)(x-3)^2=4x^2-20x+25\\\Leftrightarrow(x-3)^2=(2x)^2-2\cdot2x\cdot5+5^2\\\Leftrightarrow(x-3)^2=(2x-5)^2\\\Leftrightarrow (x-3)^2-(2x-5)^2=0\\\Leftrightarrow (x-3-2x+5)(x-3+2x-5)=0\\\Leftrightarrow (-x+2)(3x-8)=0\\\Leftrightarrow \left[\begin{array}{} -x+2=0\\ 3x-8=0 \end{array} \right.\\\Leftrightarrow \left[\begin{array}{} -x=-2\\ 3x=8 \end{array} \right.\\\Leftrightarrow \left[\begin{array}{} x=2\\ x=\dfrac{8}{3} \end{array} \right.\\Vậy:...\)
1.
$\sqrt{3x^2}-\sqrt{12}=0$
$\Leftrightarrow \sqrt{3x^2}=\sqrt{12}$
$\Leftrightarrow 3x^2=12$
$\Leftrightarrow x^2=4$
$\Leftrightarrow (x-2)(x+2)=0\Leftrightarrow x=\pm 2$
2.
$\sqrt{(x-3)^2}=9$
$\Leftrightarrow |x-3|=9$
$\Leftrightarrow x-3=9$ hoặc $x-3=-9$
$\Leftrightarrow x=12$ hoặc $x=-6$
\(a,\Rightarrow4x^2+20x+25=0\Rightarrow\left(2x+5\right)^2=0\Rightarrow2x+5=0\Rightarrow x=-\dfrac{5}{2}\\ b,\Rightarrow x^3-6x^2+12x-8=0\Rightarrow\left(x-2\right)^3=0\Rightarrow x-2=0\Rightarrow x=2\)
a) \(\Rightarrow4x^2+20x+25=0\)
\(\Rightarrow\left(2x+5\right)^2=0\Rightarrow2x+5=0\)
\(\Rightarrow x=-\dfrac{5}{2}\)
b) \(\Rightarrow x^3-6x^2+12x-8=0\)
\(\Rightarrow\left(x-2\right)^3=0\Rightarrow x=2\)